Dimensionality Expansion of a Butterfly Shaped Pd4 Framework: Constructing Edge‐Sharing Pd6 Tetrahedra. Issue 15 (14th February 2019) - Shimamoto, Kento; Sunada, Yusuke
Abstract: The construction of well‐defined transition‐metal clusters has attracted substantial attention due to their unique chemical and/or physical properties. Metal clusters with 1D or 2D structures are now accessible by template‐synthesis methods, in which multiple metal atoms are arranged with the aid of template molecules and their 1D or 2D structures. However, the rational synthesis of 3D clusters remains challenging, mostly due to a lack of appropriate template molecules. Herein, we report the rational synthesis of a 2D butterfly shaped Pd4 framework (2 ) and 3D edge‐sharing Pd6 tetrahedra (5 ) by treatment of easily available organosilicon compounds with Pd(CN t Bu)2 . The diphenylsilylene moiety thereby serves as the key component to generate the butterfly structure of the Pd4 clusters in2 . A dimensionality expansion, induced by two Cl atoms, of two butterfly shaped Pd4 subunits supported by two diphenylsilylene moieties afforded the edge‐sharing tetrahedral architecture of the Pd6 cluster in5 . Abstract : Rational synthesis of a 2D butterfly shaped Pd4 framework and 3D edge‐sharing Pd6 tetrahedra was realized by treatment of easily available organosilicon compounds with Pd(CN t Bu)2 (see scheme) The "SiPh2 " moiety serves as the key component to generate the butterfly structure of the Pd4 cluster, and a dimensionality expansion, induced by two Cl atoms, of two butterfly‐shaped Pd4 subunits afforded the edge‐sharing tetrahedral architecture of the Pd6 cluster.